Efektivitas Pestisida Nabati Daun Babadotan (Ageratum conyzoides L.) Terhadap Mortalitas Hama Wereng Coklat (Nilaparvata lugens Stal.) Pada Tanaman Padi: Effectiveness of the Vegetable Pesticide Babadotan Leaves (Ageratum conyzoides L.) Against the Mortality of Brown Planthopper Pests (Nilaparvata lugens Stal.) on Paddy Plants - ., Ajijah; Rosa, Helda Orbani; Aidawati, Noor (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Oryza sativa L. is the main food crop in Indonesia. The need for rice continues to increase every year. Rice production in South Kalimantan in 2019 reached 790,449 tons of rice, then in 2020 it decreased to 677,105 tons of rice. One of the causes of the decline in rice productivity is the attack of the brown planthopper (Nilavarpata lugens Stall.). This research aims to determine the effectiveness of the herbal pesticide babadotan leaves on the mortality of brown planthopper pests on rice plants. This research was designed using a Completely Randomized Design (CRD). The factors tested were the administration of a herbal pesticide solution of babadotan leaves at doses of 3%, 6% and 9% with a control treatment that was not given pesnab and a chemical control as a comparison. This study had 5 treatments and 4 replications. The results of the study showed that administering 9% herbal pesticide solution from babadotan leaves was effective in controlling brown planthopper pests with a mortality value of 80%.